An AP-MS- and BioID-compatible MAC-tag enables comprehensive mapping of protein interactions and subcellular localizations - Xiaonan Liu (Nature Portfolio, 2018)
AP-MS and BioID provide complementary insights into cellular protein interaction networks. To facilitate their combined use, the authors here present an AP-MS- and BioID-compatible affinity tag, enabling efficient determination of cellular protein locations and interaction distances.